Vestibular migraine in multicenter neurology clinics according to the appendix criteria in the third beta edition of the International Classification of Headache Disorders. (April 2016) - Cho, Soo-Jin; Kim, Byung-Kun; Kim, Byung-Su; Kim, Jae-Moon; Kim, Soo-Kyoung; Moon, Heui-Soo; Song, Tae-Jin; Cha, Myoung-Jin; Park, Kwang-Yeol; Sohn, Jong-Hee
Background: Vestibular migraine (VM), the common term for recurrent vestibular symptoms with migraine features, has been recognized in the appendix criteria of the third beta edition of the International Classification of Headache Disorders (ICHD-3β). We applied the criteria for VM in a prospective, multicenter headache registry study. Methods: Nine neurologists enrolled consecutive patients visiting outpatient clinics for headache. The presenting headache disorder and additional VM diagnoses were classified according to the ICHD-3β. The rates of patients diagnosed with VM and probable VM using consensus criteria were assessed. Results: A total of 1414 patients were enrolled. Of 631 migraineurs, 65 were classified with VM (10.3%) and 16 with probable VM (2.5%). Accompanying migraine subtypes in VM were migraine without aura (66.2%), chronic migraine (29.2%), and migraine with aura (4.6%). Probable migraine (75%) was common in those with probable VM. The most common vestibular symptom was head motion-induced dizziness with nausea in VM and spontaneous vertigo in probable VM. The clinical characteristics of VM did not differ from those of migraine without VM. Conclusion: We diagnosed VM in 10.3% of first-visit migraineurs in neurology clinics using the ICHD-3β. Applying the diagnosis of probable VM can increase the identification of VM.